PELAYANAN ADMINISTRASI TERPADU (PATEN) DI KANTOR CAMAT MUARA JAWA: ANALISIS PERSEPSI MASYARAKAT TERHADAP PATEN - . Fatmawati (Jurnal Administrative Reform, 2017)
This article aim to describe and analyze the Public Perceptions in Integrated Administration Service (PATEN) in Muara Jawa Sub-district Office of Kutai Kartanegara Regency. Research focus set, is public perception of service requirements, public perception of service procedure, public perception of timeliness,  public perception about facilities and infrastructure,  public perception, and public perception of technical implementers. The research method used is descriptive qualitative method. Data analysis used is Interactive Model. The result of the research shows that the public perception about the integrated administration service of the sub-district (Patent), in Muara Jawa Sub-District Office of Kutai Kartanegara Regency aplikaif still not meet the expected qualification.Keyword : Public Perception, Administrative Service